(untitled) (Biological Sciences - PJSIR, 2004)
Egg parasitoids Trichogramma chilonis were released in cotton by planting after early and late sown NIAB-86 to find out dispersing and parasitizing potential. Observations on percent parasitization were taken at distances of 1-5 meters from fixed releasing sites. It was recorded that the dispersal of T. chilonis was physically affected by crop growth and climatic conditions. The maximum dispersal and parasitization was recorded in late September and in early October. Intensity of parasitization was more after 24 h as compared to 48 h post release of parasitoids.